The Mie Theory Basics and Applications - Hergert, Wolfram; Wriedt, Thomas; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book presents in a concise way the Mie theory and its current applications. It begins with an overview of current theories, computational methods, experimental techniques, and applications of optics of small particles. There is also some biographic information on Gustav Mie, who published his famous paper on the colour of Gold colloids in 1908. The Mie solution for the light scattering of small spherical particles set the basis for more advanced scattering theories and today there are many methods to calculate light scattering and absorption for practically any shape and composition of particles. The optics of small particles is of interest in industrial, atmospheric, astronomic and other research. The book covers the latest developments in divers fields in scattering theory such as plasmon resonance, multiple scattering and optical force.
Gustav Mie and Mie theory -- Nobel nano-particles on plane surfaces and plasmon resonances -- Mie theory and Gaussian laser beam scattering -- The extension of Mie theory to multiple spheres -- Mie theory, a review -- From theories by Lorenz and Mie to ontological under-determination of theories by experiments -- Predicting the appearance of materials using Lorenz-Mie theory -- Rainbows, coronas and glories -- Optical force and torque on single and aggregated spheres: The trapping issue -- Dipole re-radiation effects in surface enhanced Raman scattering -- Mie theory extensions.
Keywords: Physics; Meteorology; Microwaves; Nanotechnology; Physics; Atomic, Molecular, Optical and Plasma Physics; Microwaves, RF and Optical Engineering; Meteorology/Climatology.; Nanoscale Science and Technology; Nanotechnology; Measurement Science and Instrumentation